Technique for Obtaining Large Complex Oxide Crystals for Experiments on Muon-to-Electron Conversion Registration in High Energy Physics - Gerasymov, Ya. (Science and Innovation, 2024)
Technological approaches for qualitative large size scintillation crystals growing based on rare-earth silicates are proposed. A method of charging the iridium crucibles using the eutectic phase instead of the oxyorthosilicate was developed.